The Prevalence of Pharmacological Neuroenhancement Among University Students Before and During the COVID-19-Pandemic: Results of Three Consecutive Cross-Sectional Survey Studies in Germany - Dietz, Pavel; Werner, Antonia M.; Reichel, Jennifer L.; Schäfer, Markus; Mülder, Lina M.; Beutel, Manfred; Simon, Perikles; Letzel, Stephan; Heller, Sebastian (Frontiers in Public Health, 2022)
Background According to the literature, the conditions of studying and living as well as the psychological, social and health behavior-related variables, which were strongly related to pharmacological neuroenhancement (PN) before the pandemic, significantly changed during the pandemic. For this reason, it is expected that the prevalence of PN among university students is higher during the pandemic compared to before the pandemic. Therefore, the present study aimed to investigate and compare the prevalence of PN among university students before and during the COVID-19-pandemic. Methods Three online surveys assessing the 12-month prevalence of PN were conducted among university students at the University of Mainz, Germany. The first survey took place in summer term 2019 (before the pandemic), the second in summer term 2020 (during the first German lockdown), and the third in summer term 2021 (after the second German lockdown). Pearson's chi-square test was used to test whether the 12-month prevalence of PN differed significantly between the three surveys. Results The 12-month prevalence of PN was 10.4% in 2019, 11.3% in 2020, and 8.0% in 2021. Chi-square tests revealed no statistical difference in the prevalence of PN between 2019 and 2020. Overall, the use of PN was lower in 2021 compared to 2019 (p < 0.0001) as well as in comparison to 2020 (p = 0.001). Only the use of cannabis slightly increased from 2019 to 2020 (7.1 vs. 8.3%) and decreased in 2021 (5.4%). At all three time points, cannabis was the most commonly used substance for the purpose of PN. Consequently, the results suggest that the prevalence of PN was highly intertwined with the prevalence of cannabis use for PN. Discussion The decrease in the prevalence of PN of around three percentage points in 2021 compared to the previous years was a surprising finding. It may be mainly due to the decrease in the prevalence of cannabis for the purpose of PN. However, the fairly high prevalence of PN of around 8% in 2021 is still an important finding that demonstrates that there is still an urgent need for prevention initiatives among university students to combat the use of PN.